Adaptive array principles - Hudson, J. E. Ph.D (P. Peregrinus on behalf of the Institution of Electrical Engineers, 1981)
The book reviews developments in the following fields: adaptive array; vector; matrix; optimal antennas; main-lobe constraints; and suboptimal array.